ANALISA GAYA KEPEMIMPINAN, KARAKTER, DAN ETNOGRAFI PEMIMPIN DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN (STUDI KASUS PADA PT. ANDHANI RELITA / SPBU 34.434.11 CILEGON) - Leni Triana; Yuliah Yuliah (LP2M Universitas Bina Bangsa, 2021)
The purpose of this study was to find out whether the leadership style, character and ethnography of the leader could improve employee performance at PT. Andhani Relita. This study uses primary data and data collection techniques are conducted by observing and interviewing directly to the research object using random sampling to several employees. The results of the study showed that the leadership style carried out does not only refer to one type of leadership, because to achieve employee performance requires the ability to lead by adjusting the conditions that occur on the ground. In addition, leaders can understand their own character and employees, so there is a fairly good emotional connection to improved work performance. The ethnography of leaders formed when implemented appropriately and in accordance with existing conditions on the ground provides significant improvements to employee performance